Many Body Effects in Elementary Processes Occurring at Solid Surfaces - Kasai, Hideaki (Science Diliman: A Journal of Pure and Applied Sciences, 2012)
In this talk we will give a brief survey of some elementary processes observable at surfaces that manifest many body effects. We begin our survey by discussing how the electron ground-state would look like in real-space at surfaces and also the mechanism behind why the surface electrons behave and look (in reference to their real-space image) as they do in the ground-state. Next we will discuss how these electrons behave when perturbed by external fields lasting for ultrashort periods of time. We then follow this with a discussion of how the dynamics of electrons would then affect the motion of adsorbates (atoms/molecules on a solid surface). Finally we will cite some possible immediate technological applications possible with this knowledge of elementary processes involving the so-called many-body effects. We will also discuss some of the possible rends or directions in doing scientific research in the century.